2014
DOI: 10.1002/oa.2386
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Body Mass in Dogs and Wolves Using Cranial and Mandibular Dimensions: Application to Siberian Canids

Abstract: Previously developed regression formulae for estimating body mass in dogs and wolves based on cranial and mandibular dimensions are evaluated using modern canid specimens of known weight at death. Some of these equations proved reliable, but others have large standard errors of estimate and likely produce unreliable mass estimates. New sets of equations for estimating body mass in dogs and wolves are produced using our datasets, including a set of equations developed from combining the dog and wolf biometric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
2
43
0
2
Order By: Relevance
“…Their body mass estimations, calculated on the basis of the length of the mandible (cf. Losey et al 2015), also overlap: the observed range for the Palaeolithic dogs is from 26 kg to 49 kg and for the Pleistocene wolves from 36 to 56 kg. Nevertheless their means clearly differ: the mean BMe for Palaeolithic dogs is 37 kg and for Pleistocene wolves is 44 kg.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their body mass estimations, calculated on the basis of the length of the mandible (cf. Losey et al 2015), also overlap: the observed range for the Palaeolithic dogs is from 26 kg to 49 kg and for the Pleistocene wolves from 36 to 56 kg. Nevertheless their means clearly differ: the mean BMe for Palaeolithic dogs is 37 kg and for Pleistocene wolves is 44 kg.…”
Section: Discussionmentioning
confidence: 92%
“…The mean and ranges of the body mass estimates (BMe) of the Předmostí canids and of the fossil and recent canid reference groups were calculated based on the regression equations given in Losey et al (2015) and Losey et al (2016). For the mandible fragment the following regression equation was used based on a combined wolf-dog set (Losey at al.…”
Section: Recent Northern Dogs (Rnd)mentioning
confidence: 99%
“…First, if a recorded body mass value for the individual was available, we used that value. Secondly, if those data were not available, we estimated body mass by measuring mandibular length and factoring this value into a regression equation for domestic dogs published by Losey et al (2014): log(body mass) = À5.259 + 3.046(log maximum mandibular length). With one exception, all values generated with this method agreed with published standards for members of the known breeds we incorporated as identified by the American Kennel Club (AKC); these standards are reliable, as it has been shown that morphometrical variation within breeds is low, and that this variation adheres closely to the standards set by AKC (Sutter et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly, techniques that do not rely on ancient DNA preservation or preservation of pristine specimens, such as complete crania, are allowing researchers to document individual life histories of canids, improving chances of identifying individuals in close contact with humans. These techniques include investigating paleopathology and trauma to clarify, for example, pack-loading and mistreatment (Losey et al 2014; and geometric morphometrics (GM) to detect biomechanical differences among canids (Drake et al 2015;Evin et al 2016;Drake et al 2017). Dietary analysis of stable isotopes may also help to identify early canids in close contact with humans (Ewersen et al 2018).…”
mentioning
confidence: 99%
“…Although an individual dog burial has been reported from the Siberian Beringian site of Ushki-1 (Dikov 1979), which dates to around 13,000 years ago (Goebel et al 2010), by all accounts these remains were identified via photograph in the 1970s and are now lost (Pitulko and Kasparov 2017), having never been confirmed as a dog or directly dated. Shoulder Height (mm) (Harcourt 1974) Body Mass (kg) (Losey et al, 2014) Body Mass (kg) (Losey et al, 2016) 1970,1977). Perino estimated the Fox Valley and Stilwell points dated to ~7000 BC (1985:136, 365), and the Agate Basin points to ~8300-8000 BC (1985:5), suggesting that more than one occupation component (~1000 years apart) may be associated with the Stilwell II Early Archaic deposits.…”
mentioning
confidence: 99%